Pengaruh Diaphragmatic Breathing exercise terhadap Kapasitas Vital Paru Pada Pasien Asma di Wilayah Kerja Puskesmas III Denpasar Utara - Anak Agung Istri Dwi Mayuni; Made Oka Ari kamayani; Luh Mira Puspita (Coping: Community of Publishing in Nursing, 2015)
Abstract. Asthma occurs due to obstruction of the breath, one of the symptoms is the shortness of breath that can increase respiratory muscle work as a compensation mechanism of the body. However, gradually the respiratory muscles will experience weakness, so that it will lose a vital capacity in asthma patients. Diaphragmatic Breathing Exercise is one of respiratory exercises that aim to increase respiratory muscle strength. This research aims to know the existence of the influence of Diaphragmatic Breathing Exercise against the vital capacity in asthma patients after a given intervention for two weeks. The design used Nonequivalent Control Group Design with a purposive sampling technique. A large sample was 30 people (15 persons and 15 persons treatment group control group). Independent T-test results of the Test are obtained by the value of the Sig p 0.000 < 0.05, which means there is a significant difference between the average difference in the vital capacity of lungs in the treatment group and the control group. So it can be concluded that there is an influence of Diaphragmatic Breathing Exercise against the vital capacity of lungs in asthma patients at Wilayah Kerja Puskesmas III Denpasar Utara.